THE EFFECT OF TIKTOK APPLICATION ON TEACHING SPEAKING ABILITY OF THE STUDENTS ELEVENTH GRADE AT SMK NEGERI 1 PEMATANGSIANTAR - Elisa May Yolanda Marbun; Basar Lolo Siahaan; Partohap Saut Raja Sihombing (RADJA PUBLIKA, 2025)
This study investigates the effect of using the TikTok application as a learning medium on the speaking ability of the eleventh-grade students at SMK Negeri 1 Pematangsiantar. Speaking is one of the most essential skills in English learning, yet many students still struggle with pronunciation, vocabulary, grammar, fluency, and comprehension. Conventional methods relying heavily on textbooks often fail to create an engaging and interactive environment, which leads to low motivation and limited speaking practice. TikTok, as a popular social media platform among teenagers, offers interactive features such as short videos and the “duet” function that can potentially enhance students’ participation and confidence in speaking. This research employed a quasi-experimental design with a pre-test and post-test control group. The sample consisted of 60 students from two classes, selected through purposive sampling. The experimental group was taught speaking using TikTok, while the control group was taught using conventional methods. A speaking test focusing on invitation expressions was administered to both groups before and after the treatment. Students’ performances were assessed based on five criteria: pronunciation, grammar, vocabulary, fluency, and comprehension. The findings revealed that students in the experimental group showed greater improvement compared to those in the control group. Statistical analysis using a t-test demonstrated a significant difference between the post-test results of both groups, indicating that the use of TikTok had a positive effect on students’ speaking ability. The results suggest that TikTok can serve as an effective learning medium to enhance students’ speaking performance, increase motivation, and support the implementation of innovative teaching strategies in English language classrooms.